Beyond Translation: Caregiver Collaboration in Adapting an Early Language Intervention - Rumper, Brooke M.; Alper, Rebecca M.; Jaen, Julia C.; Masek, Lilian R.; Luo, Rufan; Blinkoff, Elias; Mogul, Marjie; Golinkoff, Roberta Michnick; Hirsh-Pasek, Kathy (Frontiers in Education, 2021)
Spanish-speaking families in the United States must often overcome multiple challenges to support their young children’s early language development (e.g., language and cultural barriers, financial stress, limited learning resources, etc.). These challenges highlight the need for early language interventions tailored to the needs of Spanish-speaking families and developed in collaboration with them. For diverse populations, early language interventions which are both translated into the relevant language and culturally responsive are the most effective for improving child outcomes. However, few interventions meet both criteria, demonstrating a need for materials that are accessible across both language and culture. The current study describes the five-phase process of creating a linguistically and culturally relevant Spanish adaptation of Duet, an early language intervention. The adaptation of the Duet intervention modules involved multiple language experts, including Spanish-speaking developmental psychologists, a translation company, and Spanish-speaking caregivers of infants and toddlers. Fourteen caregivers were recruited to participate in two, 3-h focus groups. Input from caregivers was a particularly important step in the adaptation process, as caregivers hold knowledge about everyday experiences with their children. Through this process, the authors aim to shed light onto the importance of collaborating with the community and present a possible framework for others who are adapting interventions.